Expectations of reciprocity when competitors share information: Experimental evidence - Bernhard Ganglmair; Alex Holcomb; Noah Myung (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Informal exchange of information among competitors has been well-documented in a variety of industries, and one's expectation of reciprocity shown to be a key determinant. We use an indeterminate horizon centipede game to establish a feedback loop in the laboratory and show that an individual's beliefs about the recipient's intentions to reciprocate matter more than a recipient's ability to do so. This implies that reducing strategic uncertainty about a competitor's behavior has a stronger effect on information ows than reducing environmental uncertainty (about the competitor's ability). We further show results on the formation of beliefs and discuss managerial implications.
Keywords: O33; D8; C72; C91; 330; knowledge diffusion; information sharing; reciprocity; conversation; experimental economics; centipede game